Pengaruh Profil Berwirausaha dan Dukungan Kerja Keluarga Terhadap Kinerja Karyawan PT ABMAG Kota Metro - Devi Novita Sari; Suwarto; Fitriani (Universitas Muhammadiyah Metro, 2026)
Based on field findings, fluctuations in company partners were found to be caused by suboptimal employee performance. Therefore, the purpose of this study was to determine the effect of entrepreneurial profile and work-family support on employee performance at PT ABMAG Kota Metro. This research was quantitative. The explanatory survey method used a saturated sample, with 73 PT ABMAG employees. A 60-item Likert-type questionnaire was used as a measurement tool, and multiple regression analysis was used. The results showed that entrepreneurial profile had a positive and significant effect on employee performance at PT ABMAG Kota Metro. Work-family support had a positive and significant effect on employee performance at PT ABMAG Kota Metro. Both entrepreneurial profile and work-family support had a positive and significant effect on employee performance at PT ABMAG Kota Metro.